2017
DOI: 10.1177/0897190017692920
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hypertriglyceridemia Induced by Sirolimus Treated With Medical Management Without Plasmapheresis: A Case Report

Abstract: Sirolimus-induced severe hypertriglyceridemia can be managed with oral lipid-lowering agents without plasmapheresis. Clinician needs to be aware of the importance of baseline and regular triglyceride monitoring in patients on sirolimus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…44 Severe hypertriglyceridemia with the use of mTOR inhibitors has been reported. 45,46 Clinical trials comparing mTOR inhibitors with CNIs have also shown that mTOR inhibitors are associated with higher levels of triglycerides, low-density lipoprotein cholesterol (LDL-C), and total cholesterol. [47][48][49] It remains unclear if mTOR inhibitor-induced hypertriglyceridemia is directly related to exposure (area under curve) or drug trough levels; however, regardless of this controversy, transplant recipients are at an increased risk of hypertriglyceridemia with mTOR inhibitors.…”
Section: Hypertriglyceridemia In Ktrsmentioning
confidence: 99%
“…44 Severe hypertriglyceridemia with the use of mTOR inhibitors has been reported. 45,46 Clinical trials comparing mTOR inhibitors with CNIs have also shown that mTOR inhibitors are associated with higher levels of triglycerides, low-density lipoprotein cholesterol (LDL-C), and total cholesterol. [47][48][49] It remains unclear if mTOR inhibitor-induced hypertriglyceridemia is directly related to exposure (area under curve) or drug trough levels; however, regardless of this controversy, transplant recipients are at an increased risk of hypertriglyceridemia with mTOR inhibitors.…”
Section: Hypertriglyceridemia In Ktrsmentioning
confidence: 99%
“…Expert opinion and anecdotal case reports provide hints on how to proceed [22]. Kido et al reported on a pharmacological approach in an index patient without signs of hyperviscosity syndrome [32]. Furthermore triglyceride levels were lower (4425 mg/dl).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of cyclosporine on triglyceride levels is relatively mild, increasing by 50 mg/dl in one study (103), but triglyceride levels were >400 mg/dl in 14% to 25% of patients with sirolimus in one report of renal transplant recipients (104) and in another in 28% of sirolimus and 35% of everolimus treated patients (105). Both sirolimus and everolimus have been associated with the development of severe HTG (106,107). These agents increase APOC3 levels and inhibit LPL (108,109).…”
Section: Immunosuppressive Agentsmentioning
confidence: 97%